Foundations of global business : a systems approach - Asgary, Nader H.; Frutos-Bencze, Dina; Samii, Massood (Emerald Publishing Limited : Information Age Publishing Inc., 2016)
In the past three decades a number of important changes have made international business more complex and exciting. The rapid and continuous changes in information and communications technology (ITC), reduced trade barriers among countries, and regionalization have increased the links and dependency among firms from various countries. This has created opportunities for increasing expansion to new markets and increasing global integration while simultaneously posing many challenges.This book views international business as a complex and integrated system and takes a systems approach to study and analyze the changes thus enabling readers to assess global business opportunities and risk in a comprehensive and integral manner. The topics presented in this book allow practitioners, scholars, and students of international business to have a broad understanding of the most relevant issues in a changing international environment.